2011 IEEE Virtual Reality Conference 2011
DOI: 10.1109/vr.2011.5759435
|View full text |Cite
|
Sign up to set email alerts
|

Improving the realism in motion-based driving simulators by adapting tilt-translation technique to human perception

Abstract: While modern dynamic driving simulators equipped with six degrees-of-freedom (6-DOF) hexapods and X-Y platforms have improved realism, mechanical limitations prevent them from offering a fully realistic driving experience. Solutions are often sought in the "washout" algorithm, with linear accelerations simulated by an empirically chosen combination of translation and tilt-coordination, based on the incapacity of otolith organs to distinguish between inclination of the head and linear acceleration. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The process of testing the platform is firstly done by performing simulation separately between roll and pitch planes, wherein incremental angle input (𝜃) is fed to (9). The range of angle input (𝜃) is Figure 8.…”
Section: Experimental Results: Accuracy and Sensitivity Of The Platformmentioning
confidence: 99%
See 2 more Smart Citations
“…The process of testing the platform is firstly done by performing simulation separately between roll and pitch planes, wherein incremental angle input (𝜃) is fed to (9). The range of angle input (𝜃) is Figure 8.…”
Section: Experimental Results: Accuracy and Sensitivity Of The Platformmentioning
confidence: 99%
“…Jefiza et al [23] and Al-Dahan et al [24] used the MPU6050 module to detect the fall of the elderly when walking, while Rifajar and Fadlil [25] used it to detect the fall of a dancing robot by monitoring the acceleration of rotational motion. The approach to measuring joint angles in this research is different, where the measured orientation is used to calculate joint angles of the DC actuators based on (9).…”
Section: Platform Testing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if this technique is not correctly implemented, it may generate an inaccurate motion perception, as it does not correspond to a natural driving movement. In addition, other studies have shown that the tilt perception thresholds must be adapted according to the level of acceleration to improve realism [3]. This leads us to believe that some participants may have been influenced not only by the type of model used in each strategy but also by the cueing strategy itself.…”
Section: B Autonomous Versus Fd Modementioning
confidence: 98%
“…One of the approaches aiming at solving these problems has been to integrate human motion perception into the control design. Most MCAs use human perceptive system information to restore additional linear acceleration while tilting the platform cockpit [3]- [6]. This is a well-known technique named tilt coordination.…”
mentioning
confidence: 99%